Disproportionate exercise load and remodeling of the athlete's right ventricle - La Gerche, A.; Heidbüchel, H.; Burns,T.; Mooney, D. J.; Taylor, A. J.; Pfluger, H. B.; Inder, W. J.; Macisaac, A. I.; Prior, D. L. (Medicine & Science in Sports & Exercise, 2011)
Purpose: There is evolving evidence that intense exercise may place a disproportionate load on the right ventricle (RV) when compared with the left ventricle (LV) of the heart. Using a novel method of estimating end-systolic wall stress (ES-s), we compared the RV and LV during exercise and assessed whether this influenced chronic ventricular remodeling in athletes.